Characteristics of microbial communities and intestinal pathogenic bacteria for migrated Larus ridibundus in southwest China. Issue 4 (5th July 2018) - Liao, Feng; Gu, Wenpeng; Li, Duo; Liang, Junrong; Fu, Xiaoqing; Xu, Wen; Duan, Ran; Wang, Xin; Jing, Huaiqi; Dai, Jiejie
Abstract: Larus ridibundus, a migratory wild bird, has become one of the most popular gull species in southwest China in recent years. There has been no information on the gut microbiota and intestinal pathogenic bacteria configuration in wild L. ridibundus, even though the public are in close contact with this bird. In this study, 16S rRNA amplicon‐sequencing methods were used to describe the microbial community structure and intestinal pathogenic bacteria were isolated to identify their characteristics. The taxonomic results revealed that Firmicutes (86%), Proteobacteria (10%), and Tenericutes (3%) were the three most abundant phyla in the gut of L. ridibundus . Enterococcaceae, Enterobacteriaceae, and Mycoplasmataceae were the most predominant families, respectively. The number of operational taxonomic units (OTUs), the richness estimates and diversity indices of microbiota, was statistically different ( p < 0.05). However, beta diversity showed that no statistical significance ( p > 0.05) between all the fecal samples. The most frequently isolated intestinal pathogenic bacteria from L. ridibundus were enteropathogenic Escherichia coli (32%) and Salmonella (21%). Pulsed‐field gel electrophoresis (PFGE) results of Salmonella species revealed a high degree of similarity between isolates, which was not observed for other species. None of the potentially pathogenic isolates were identical to human‐isolated counterparts suggesting that there was little cross‐infection between humans and gulls, despite close proximity. In brief, this study provided a baseline for future L. ridibundus microbiology analysis, and made an understanding of the intestinal bacterial community structure and diversity. Abstract : In this study, metagenomic methods were used to describe the microbial community structure and intestinal pathogenic bacteria were isolated to identify their characteristics isolated from migrated Larus ridibundus . These results created a baseline for future L. ridibundus microbiology research, and make an understanding of the intestinal bacterial community structure and diversity.